Oncogenic osteomalacia secondary to hemangiopericytoma: a case report - Matin, Aamir; Tuse, Sushant Sopan (International Journal of Research in Orthopaedics, 2021)
We are going to present a case of hypo-phosphatemic rickets secondary to phosphaturic mesenchymal tumour who came with complaints of proximal muscle weakness which limited his effort tolerance and activities of daily life like standing from squatting position and rib pain. His FGF-23 levels were very high above normal levels and PET CT revealed a well-defined enhancing lesion abutting femoral neurovascular bundle. After consultation with endocrinologist, we have d done complete excision of the mass. Post-surgery all symptoms were relieved, proximal muscle strength improved gradually and serum levels of phosphorus, ALP and FGF-23 came back to normal.